Development of Powtoon Application-Based Animated Videos on Hajj and Umrah Material at Middle School - Nanda, Islamia; Riawarda, Andi; Sunusi, Syamsu (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study intends to analyze the development stages of animated videos created using the Powtoon application for Hajj and Umrah material, as well as to evaluate the practicality and effectiveness of these animated videos. This study uses a development research approach with the ADDIE development model. The subjects of this study were Fiqh teachers and students of grade 8 at the Middle School, or Madrasah Tsanawiyah Suli, with a total of 22 students. The data collection techniques were interviews, observations, questionnaires, and documentation. This study employed a mixed-methods data analysis technique. The feasibility test results indicated that the material expert validator scored 81.81% in the "very valid" category, media experts scored 97.5% in the "very valid" category, linguists scored 75% in the "valid" category, Islamic jurisprudence subject teachers' practicality questionnaire received a score of 95.45% in the "very practical" category, and students' practicality questionnaire received a score of 91.43% in the "very practical" category. The development of Powtoon-based animated videos for Hajj and Umrah material has proven effective because it increases learning motivation and makes it easier for students to understand the Hajj and Umrah material. The use of Powtoon-based animated video learning media has demonstrated an increase in learning motivation and student understanding.